The Effectiveness of Skimming and Scanning Strategies in Improving Comprehension and Reading Speed Rates to Students of English Study Programme - Iwan Fauzi (Register Journal, 2018)
This research was aimed to know the effectiveness of skimming and scanning strategies to improve students’ reading ability indicated by their competence to comprehend texts and their performance in the speed of reading. Pretest-posttest control group design was used in this research. Third year students of English Study Programme of FKIP of Palangka Raya University were taken to the reasearch subject. There were 54 students taken which were equally in number grouped into an experimental group and a control group. Both groups were considered to be equal in reading performance with regard to the result of pretest carried out before the experiment. Experimental group was the class where the researcher supervised it, and control group was a group where he did not supervise it with the experiments. The result showed that scores of reading tasks given to the experimental group were significantly different with the control group in which t-value was 9.928 with the significance (2-tailed) value was p0.05. Meanwhile, the speed of reading rates of the experimental group was also significantly different with that of in the control group where t-value was 9.325 with the significance (2-tailed) value was p0.05. Either comprehension or speed rates performed by experimental group showed more excellent than its counterpart. Based on these findings, skimming and scanning strategies were undeniably effective to improve students’ comprehension in reading and efficient to boost their reading speed.Keywords:  Reading comprehension; Reading speed; Skimming; Scanning